Blood donation in surgical procedures: Experience in a hepatic transplantation reference service in the Northeast - Gomes, Juliana dos Santos; Silva, Maria José da; Figueiredo, Eliane Souza; Moutinho, Luiz Eduardo Rafael; Fonseca Neto, Olival Cirilo Lucena da; Lacerda, Cláudio Moura (Brazilian Journal of Transplantation, 2019)
Introduction: Using blood products plays an essential role in medical practice and adequacy of blood stocks is vital in preventable deaths. The availability of this resource absolutely depends on donation from another individual, and recruitment and retention of blood donors can be a public health challenge. Purpose: This article aims to reiterate the importance of intensifying professional strategies that can, through a specific targeted audience to increase supply of blood components in transfusion centers. Methods: This cross-sectional observational study included patients who underwent surgery in liver transplant unit at Hospital Universit rio Oswaldo Cruz (Recife/PE). Data on sociodemographic profile, procedures performed and use/replacement of blood products were analyzed. Results: 35 patients were interviewed, of which 32 (91.4%) used blood components. Liver transplantation was absolutely prevalent in the studied group (94.2%). 77.1% of patients who used blood components did not make replacement donation and all (100%) of then claimed it was not professionally requested by the institution. Conclusion: This study shows the importance of institutional planning for attracting blood donors linked to patients. In fact, social responsibility and educational campaigns are the key marketing strategies related to blood donation. However, coordination between programmed donor demand and development of collective and individual activities must be exercised in a broad context of the health system in order to improve blood donation practices.